(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: There are different sources of economic growth, including domestic savings for capital formation. Domestic savings mobilized into the expansion of productive capacity of an economy adds economic growth and thereby reinforces investment and savings. Gross savings and capital formation matter for the economic growth of Nepal. Objective: The study’s main objective is to inspect the nexus between gross domestic saving, gross capital formation, and economic growth in Nepal. Methodology: This study uses the Auto-Regressive Distributive Lag (ARDL) approach to cointegration. Zivot-Andrews (ZA) unit root test has been used to check for a structural break in data, and the Bounds test has been carried out to explore the existence of a long-run association between variables. Results: The empirical outcomes pointed out a positive and significant long-run relationship between gross domestic savings, gross capital formation, and economic growth in Nepal. Zivot-Andrews unit root tests reveal a structural break in the data set. Causality result indicates a unidirectional linkage from gross investment to growth, economic growth to gross domestic saving, and a bidirectional linkage between gross domestic savings and gross investment. Conclusion: The study concludes that an increase in the productive capability through increased saving and investment in the productive sector helps increase the economic growth in Nepal. So, gross domestic savings, gross investment, and economic growth are associated in the long run with one structural break. Implications: The study implies that real economic growth in Nepal can be enlarged if the government of Nepal focuses on an increase in saving and make strong provisions for mobilizing and investing such savings into productive sectors of the economy. Originality: This paper is original and has not been published in other publications. Similarly, no financial support has been received while working on this paper. Paper Type: Research paper